Wisata Buatan di Meruyung sebagai Lokasi Pembelajaran Berwirausaha Berdasarkan Persepsi Masyarakat - Siti Marti'ah; Berta Dian Theodora (Universitas Indraprasta PGRI Jakarta, 2017)
The tourist attractions developed in Depok are not only nature and heritage tourism, but also artificial tourism. For example, Mosque of golden dome (masjid kubah emas) is used not just for place or worship, but it is also used by visitors as a religious tourism. The visitors’ great curiosity about this mosque makes it one of favorite tourism destinations of people in Depok and Jabodetabek. The research is aimed at identifying the concept of community participation in the development of artificial tourism in Meruyung subdistrict (2) the concept of tourism development in Meruyung and its effects on economic life of surrounding community. The research applies a qualitative approach. The samples are taken using snowball sampling, in which the subdistrict head of Meruyung becomes the main resource person. The existence of the mosque as a religious tourism is an added value that can be experienced by visitors during their visit. Many visitors come with different reasons such as 1) to direcly see the mosque with a gold-plated dome 2) to perform prayer, 3) to sightsee, 4) to see the mosque architecture. Visitors and community agree to call the mosque of golden dome a tourist site , as seen in the percentage of answers showing that 98% (18% strongly agree and 80% agree) of the community agrees to call it a tourist site, and 97% (12% strongly agree and 85% agree) of the community agrees to have made this mosque a place to earn income, as seen from the result of questionnaires distributed to local vendors showingthat they are given opportunity by local vendor management to sell things in the area of the mosque of golden dome.